The cooperative intercultural pragmatics of request strategies model (CIPRS): a study on request strategies by second language learners in a multicultural setting - Mokhtar, Nor Zainiyah Norita (IIUM Press, International Islamic University Malaysia, 2017)
This book is focus upon differences in the choice of request strategies opted by second language learners in a higher education institution with a multilingual and multicultural setting. It has been observed by several studies carried out in this field that second language learners would probably choose different types of strategies when making requests. Apart from identifying the request strategies, I also aim to examine the linguistic forms that are being used by second language learners when making requests and whether they vary them according to the social events presented to them. At the same time, I am also concerned with the manner as to how a second language learner would address their hearer within the social context, for instance how they would request information or favours from strangers or friends or families or from someone who hasa higher position, with regard to social status. in addition to that, I would also like to find out why they chose to utter their requests as in the way they did and what motivates them.